Paths to a middle ground : the diplomacy of Natchez, Boukfouka, Nogales, and San Fernando de las Barrancas, 1791-1795 - Weeks, Charles A., 1937- (UPCC book collections on Project MUSE., 2005)
Charles Weeks explores the diplomacy of Spanish colonial officials in New Orleans and Natchez in order to establish posts on the Mississippi River and Tombigbee rivers in the early 1790s. Another purpose of this diplomacy, urged by Indian leaders and embraced by Spanish officials, was the formation of a regional Indian confederation that would deter American expansion into Indian lands. Weeks shows how diplomatic relations were established and maintained in the Gulf South between Choctaw, Chickasaw, Creek, and Cherokee chiefs and their Spanish counterparts aided by traders who had become integr.